2021
DOI: 10.1108/jbim-07-2020-0326
|View full text |Cite
|
Sign up to set email alerts
|

Impact of digital technology on velocity of B2B buyer-supplier relationship development

Abstract: Purpose This study aims to examine how the widespread adoption of digital technology (DT) in business-to-business (B2B) markets affects and, in particular, increases the velocity of relationship development over time. Design/methodology/approach A literature search was conducted to develop propositions concerning DT’s effect on the various stages of an existing B2B buyer-seller relationship development model. A group of 55 experienced practitioners was used to obtain reactions to the propositions. Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 91 publications
2
24
0
Order By: Relevance
“…Nevertheless, for B2B customers, physical surroundings were found more relevant than digital touchpoints in determining the evaluation of the moment of truth. It is true that digital touchpoints have become ever more prevalent for business customers as well (Kauffman and Pointer, 2021), yet our findings indicate that the physical environment is still more important. Yet, it remains to be seen if this will still be the case in the near future.…”
Section: Theoretical Contributionsmentioning
confidence: 72%
See 1 more Smart Citation
“…Nevertheless, for B2B customers, physical surroundings were found more relevant than digital touchpoints in determining the evaluation of the moment of truth. It is true that digital touchpoints have become ever more prevalent for business customers as well (Kauffman and Pointer, 2021), yet our findings indicate that the physical environment is still more important. Yet, it remains to be seen if this will still be the case in the near future.…”
Section: Theoretical Contributionsmentioning
confidence: 72%
“…They present both challenges and opportunities for customer relationship management . Companies usually try to develop digital relationships with their customers, as these touchpoints are highly interactive and generate engagement (Vieira et al, 2019;Kauffman and Pointer, 2021). For that matter, customers depend on digital forms of contacting during their service encounter (Bacile, 2020).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…However, despite growing interest in this phenomena within B2B customer behaviour literature (Alonso-Garcia et al , 2021a, 2021b; Aichner and Gruber, 2017; Pawlowski and Patuszak, 2016), OCM research is still in its infancy (Palmatier et al , 2019; Berman and Thelen, 2018; Cummins et al , 2016; Juaneda Ayensa et al , 2016) and the B2B customer perspective has rarely been studied (Alonso-Garcia et al , 2021a, 2021b; Forrester, 2015). Emerging OCM literature which adopts a B2B perspective reveals an under-examined strategic capability in areas such as logistics and distribution (Wieczerniak and Milczarek, 2019), the infiltration of technology (Fujimura and Ishino, 2020), the advancement of B2B omni-channel (OC) management (Alonso-Garcia et al , 2021a, 2021b) and the impact of digital technology on B2B buyer-supplier relationship development (Kauffman and Pointer, 2021; Gavin et al , 2020), reinforcing the need to systematically review what has been found to date.…”
Section: Introductionmentioning
confidence: 99%
“…This research provides much-needed conceptualisation of strategies for business-to-business industry customer (B2B customer) marketing campaign development across the omni-channel in the digital era. This era is characterised by technology encompassing a myriad of e-business tools that can be beneficially used by B2B marketers to enhance commercial buyer-seller relationships (Kauffman and Pointer, 2021) as electronic means of trade between companies continue to grow in strength and dynamics (Pawlowski and Patuszak, 2016). Omni-channel marketing (OCM) is an emerging strategic phenomena, driven in part by the integration of digital into all aspects of business life (Spencer and Sutton-Brady, 2021), as business buyers are increasingly adopting digital touchpoints (Pawlowski and Patuszak, 2016; Forrester, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation